Perancangan Sistem Informasi SMS Gateway Berbasis Web dalam Meningkatkan Layanan Komunikasi pada PT. Perdana Jatiputra - Ucok Darmanto Soer; Ikhsan Romli (DPPM Universitas Pelita Bangsa, 2020)
One model reliable communication today is a short message short messaging system (SMS). This means that SMS should be able to conduct transactions with the database. For it is necessary to build a system called SMS Gateway. In principle, SMS Gateway is a software that uses the help computers utilizing mobile technologies are integrated in order to distribute the messages that are generated by the system information via SMS media that are handled by the cellular network. SMS Gateway is a media that can provide solutions in the delivery of information quickly and easily, applied in an effort to improve the quality of work and information and communication services in handling problems that exist in PT Perdana Jatiputra. So through the SMS media admin does not need to provide information to one by one employees through telphon or use a piece of paper to make important announcements. The result of this research is that SMS gateway can simplify the effort to improve the quality of service especially in the effort of equalization of information to all employees of PT Perdana Jatiputra. Keywords: SMS Gateway, Information System, User Interface, Gammu.